2016
DOI: 10.1080/10095020.2016.1151212
|View full text |Cite
|
Sign up to set email alerts
|

Event-driven flood management: design and computational modules

Abstract: Flood management is a set of activities that have to be carried out in collaboration with multiple agencies. Advanced flood information with early warning generated using remote sensing satellite technologies can help the agencies to effectively manage the situation on ground. Various environmental parameters and forecasts provided by different agencies can be analyzed and compared with historical flood events for generating probable flood event alerts. The information (environmental parameters) provided by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…A series of satellite-derived global precipitation datasets have been developed, such as the Climate Precipitation Center morphing method [4], Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks [5], the Global Satellite Mapping of Precipitation Project [6], and TRMM Multi-Satellite Precipitation Analysis (TMPA) [7] products. Among these datasets, TMPA products, which have a relatively high level of accuracy, have been used widely [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…A series of satellite-derived global precipitation datasets have been developed, such as the Climate Precipitation Center morphing method [4], Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks [5], the Global Satellite Mapping of Precipitation Project [6], and TRMM Multi-Satellite Precipitation Analysis (TMPA) [7] products. Among these datasets, TMPA products, which have a relatively high level of accuracy, have been used widely [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Various news channels and newspapers are providing their live newsfeeds on Internet in Rich Site Summary or Really Simple Syndication (RSS) and Geo RSS formats. Sharma et al (2016) have proposed a framework in which they have used observed TRMM data to generate the probable flood events. The developed system is generating current-day, past 1-day, 2-day and 3-day products over Indian region using TRMM data.…”
Section: Introductionmentioning
confidence: 99%
“…It will increase the time frame window of current-day and past 3 days products to past 3 days, current-day and future 3 days products. By considering Sharma et al (2016) as a base work, this study has been proposed to generate automated integrated TRMM and GEFS spatial products coupled with live news available as rich site summary (RSS) feeds using open-source technologies to identify probable high rainfall events over Indian region, on which the satellite data can be planned for acquisition. The satellite data planned using the above method can be used for delineating flood using GIS software and techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are four logical layers in the event processing flow, namely, the event generator, the event channel, the event processing engine and the downstream event-driven activity [39]. The event-driven method can play an important role in the management and monitoring of hydrological disasters [40]. Figure 2 illustrates the event-driven mechanism.…”
Section: Sensor Web and Event-driven Mechanismmentioning
confidence: 99%